From car sickness to autonomous car sickness: A review. (April 2019) - Iskander, Julie; Attia, Mohammed; Saleh, Khaled; Nahavandi, Darius; Abobakr, Ahmed; Mohamed, Shady; Asadi, Houshyar; Khosravi, Abbas; Lim, Chee Peng; Hossny, Mohammed
Highlights: A customisable solution is the only viable solution to mitigate motion sickness. The proposed motion sickness resilient framework consists of three main components. A passenger-centric component which registers the human physiological state. A vehicle-centric component to register vehicle state and adjust in-car environment. An infotainment system with smart AV apps which are motion resilient. Abstract: Motion sickness comprises a set of symptoms, such as nausea, headaches, and disorientation, that affects healthy individuals when undergoing different types of motion, including virtual motion. The ways of mitigating motion sickness is a controversial issue as it strongly depends on variability among individuals due to anthropometric, physical as well as physiological traits, making it difficult to identify and derive a universal solution. With the introduction of autonomous vehicles, we are moving from car sickness, which is motion sickness induced when riding in cars, to autonomous car sickness, which arises from riding in autonomous vehicles. To ensure advancement of fully-autonomous vehicles, a comfortable experience must be provided to the passengers. An important factor that affects the acceptance of autonomous cars is the capability of passengers to perform non-driving tasks like reading, relaxing, and/or socialising in a comfortable style with no or limited motion sickness symptoms. Drivers, who never suffer from motion sickness while driving, might be, when riding as passengers in autonomous cars, susceptible to motion sickness due to the lack of controllability on the vehicle in addition to sensory conflicts. Therefore, in-depth investigations on the causes of autonomous car sickness are required. In this paper, we present different theories explaining the 'how' and 'why' of motion sickness and then discuss whether these factors are applicable to autonomous car sickness. The adaptation of different motion sickness predictors that can be used to limit autonomous car sickness are also discussed, with a proposal of a framework that provides a viable solution to mitigate autonomous carsickness.